Humor in english literature - Frisbie, Isabella Russell (My University, 1894)
Introduction: It has been written that; “Intention is necessary to art; that if life be a lesson so easily read by him that runs, wherein is the advantage of letters at all? The careless do not read the lesson of life: it is the function of the true artist whom we take to be the humorist, to point the moral, and we say that by the manner in which he does so he shows his skill.” But what is humor? To define it proves almost impossible. It is a something which has to do with the most subtle workings of our intellect and motions. Everyone knows how difficult it is to explain a bit of humor, for in the attempt to analyze, all the spice is lost. It has been described not defined by that eminent divine of the seventeenth century, Dr. Barrow, as; “Tis that which we all see and know; anyone apprehends what it is by acquaintance, better than I can inform him by description. It is, indeed a thing so versatile and multiform, appearing in so many postures, so many garbs, so variously apprehended by several eyes and judgments, that it seemeth no less hard to settle a clear and certain notion thereof, than to make a portrait of Proteus, or to define the figure of a fleeting air”.
Citation: Frisbie, Isabella Russell. Humor in english literature. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: English; Literature; Humor; Word; Theses; Manuscripts (documents)